In patients with suspected rheumatoid arthritis, does the addition of musculoskeletal ultrasound increase the ability of rheumatologists to confirm or rule out a diagnosis of rheumatoid arthritis at an earlier stage compared to conventional diagnostic assessment alone?. ([2017]) - Harbour, Jenny
No abstract available